New methodological perspectives for the teaching of Chemistry: Practice and theory contextualized with everyday life / Novas perspectivas metodológicas para o ensino de Química: prática e teoria contextualizada com o cotidiano - Anderson Soares de Almeida; Aldenir Feitosa dos Santos (Universidade Estadual de Alagoas, 2018)
The educational field has directed its eyes towards a teaching that integrates the contextualization of the daily theme in theoretical classes and practices of chemistry, in order to provide an improvement of the teaching-learning process in the formation of a citizen. The present research aimed at the acquisition of theoretical-practical classes of chemistry in a daily context as a methodological proposal for high school students. Chemistry classes were elaborated with subjects that were difficult to understand for the students contextualizing with daily facts and practices of chemistry, these practicaltheoretical classes were applied to students of the state network of the city of Arapiraca-AL. It was observed that the classes stimulated the students significantly, because before the lesson the percentage of correct answers of the questionnaires applied was only 19.43% and after the frequency of correct answers passed to 70.14%. Facing this, it is emphasized that the classes in a context of daily life associated with practice and theory, motivate the students and corroborate with the teaching-learning process that underlies their formation.